2022
DOI: 10.1080/15502783.2022.2053300
|View full text |Cite
|
Sign up to set email alerts
|

The ergogenic effect of acute carnosine and anserine supplementation: dosing, timing, and underlying mechanism

Abstract: Background Recent studies suggest that acute-combined carnosine and anserine supplementation has the potential to improve the performance of certain cycling protocols. Yet, data on optimal dose, timing of ingestion, effective exercise range, and mode of action are lacking. Three studies were conducted to establish dosing and timing guidelines concerning carnosine and anserine intake and to unravel the mechanism underlying the ergogenic effects. Methods First, a dose res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Therefore, the current study investigates the effects of acute preexercise balenine supplementation on different performance types of maximal and submaximal intensity in humans. In line with previous research into acute carnosine and anserine supplementation (Barbaresi et al, 2021;Blancquaert et al, 2021;de Jager et al, 2022), we expect an improvement in maximal performance such as cycling sprints, maximal voluntary contractions and a short, high-intensity time trial. Moreover, as the mechanism responsible for the observed effects with acute carnosine and anserine supplementation remains unclear, an exploration of potential effects on a long-lasting high-intensity performance is conducted.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, the current study investigates the effects of acute preexercise balenine supplementation on different performance types of maximal and submaximal intensity in humans. In line with previous research into acute carnosine and anserine supplementation (Barbaresi et al, 2021;Blancquaert et al, 2021;de Jager et al, 2022), we expect an improvement in maximal performance such as cycling sprints, maximal voluntary contractions and a short, high-intensity time trial. Moreover, as the mechanism responsible for the observed effects with acute carnosine and anserine supplementation remains unclear, an exploration of potential effects on a long-lasting high-intensity performance is conducted.…”
supporting
confidence: 83%
“…Note repeated short cycling sprints, 30-s Wingate tests, maximal isometric contractions, and in a 8-min cycling TT (Barbaresi et al, 2021;Blancquaert et al, 2021;de Jager et al, 2022;Suzuki et al, 2004). Should the functionality of balenine resemble that of carnosine and anserine, an improved peak power, peak torque, and 4 km time trial (which closely resembles the 8-min TT) would be expected and be even more pronounced because of the better bioavailability of balenine (de Jager et al, unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue remains largely unclear in humans, in which high activity of the CN1 enzyme quickly degrades circulating carnosine (2). It has long been suggested that circulating HCDs are extremely low or absent in human plasma (43-45), although more recent reports already detected carnosine (46, 47). We now demonstrate that N-acetylcarnosine is the most stable carnosine analog in plasma, indicating that acetylation of the β-alanine residue protects against the hydrolyzing activity of CN1.…”
Section: Discussionmentioning
confidence: 99%
“…L-Cit increased the carnosine concentration under TNZ, whereas, this was diminished under HS condition. The influence of L-Cit on these peptides is not fully ascertained but may be related to their role in muscle physiology since both peptides are involved in skeletal muscle homeostasis ( Blancquaert et al, 2016 ; Suidasari et al, 2016 ; de Jager et al, 2022 ). Furthermore, 3-methylhistidine is an amino acid found in actin and myosin, and over 90% of its body pool is present in the skeletal muscle ( Williams, 2003 ).…”
Section: Discussionmentioning
confidence: 99%